Histopathological Evaluation of the Embryo and Weight Assessment of Body, Kidney, and Liver in Pregnant NMRI Mice Exposed to Zinc Oxide (ZnO)Nanoparticles - Bagher Seyedalipour; Masumeh Oshrieh; Ramezan Khanbabaee (Fasa University of Medical Sciences, 2015)
Background & Objective: Zinc is an essential trace element which plays a key role in the growth and the development of the embryo during pregnancy. This study was designed to investigate the cytotoxic effects of zinc oxide nanoparticles on embryonic development and to assess the weight of body, kidney, and liver in Naval Medical Research Institute (NMRI) mice.   Materials & Methods: 25 female of NMRI mice weighting 30±3.0 gram were randomly divided into five groups (five in each group, four experimental groups and one control group). Mice in experimental groups one, two, three, and four received intraperitoneal ZnO nanoparticle with the concentrations of 50,100,150, and 200 mg / kg, respectively during 15 days (every other day). At the end, the weight of the body, the kidney, and the liver of the pregnant mice and the embryos were measured. In addition, histopathological evaluations were performed on embryos. The data were analyzed by SAS software in P≤0.05.   Results: Based on the macroscopic observations, the embryo and the kidney weights decreased and increased, respectively with increasing different concentrations of nanoparticle compared with controls (P≤0.05). Our data showed that at different concentrations of nanoparticles, the distance, the size, and the number of vertebral bodies increased compared to the control group. At the concentration of 150 mg/kg, an accumulation of mesenchymal cells for cartilage were observed and it seems that high dose of nanoparticles prevents embryo growth. Conclusion: The results of this study indicate that ZnO nanoparticles cause embryonic developmental delay, undifferentiated and disorganized vertebral bodies in NMRI mice.